Thailand Energy Scenarios: Pathways towards Carbon Neutrality 2050 - Pongthanaisawan, Jakapong; Wangjiraniran, Weerin; Nakapreecha, Nitida (International Journal of Energy Economics and Policy, 2023)
“Carbon neutrality” has become a challenging target for the energy sector, which may lead to a major structural redesign of the sector. This may inevitably have an impact on the country’s economic structure. Future policies should be carefully formulated, taking into consideration both the positives and negatives, as well as the short-and long-term effects on the nation’s energy and economy in the future. This will ensure that the nation receives the maximum benefit in terms of energy security, carbon targets, environmental and social care, and sustainable economic growth. The various driving factors to achieve carbon neutrality by 2050 were analyzed based on the STEEP analysis, with an emphasis on the energy sector, which is found to make the largest contribution to greenhouse gas emissions. It found that political will, green technology, and financial incentives are the most influential factors in achieving the carbon neutrality target. These factors are considered as critical uncertainties when building two future scenarios for the energy sector. The Classic scenario reflects the attempt to achieve carbon neutrality with an emphasis on clean technologies, such as renewable energy, green hydrogen, and carbon capture, utilization, and storage (CCUS). Meanwhile, the target will become even more challenging when energy efficiency is to be increased, such as electric vehicle. The Orchestra scenario shows how energy management, a decentralized energy system and promoting the prosumer market, especially in the residential sector, are used to try to reach carbon neutrality. In conclusion, both scenarios may result in the achievement of the 2050 carbon neutrality target. The Orchestra scenario may need planning, a holistic management approach, and active cooperation from various sectors. On the contrary, in the Classic scenario, most activities are restricted to the energy sector, which may entail some risks, particularly the rising demand for carbon offsets from other countries.